Evaluation Of The Use Of The Mannheim Peritonitis Index (MPI) As A Predictor Of Mortality And Morbidity In Peritonitis Patients Due To Hollow Organ Perforation At Kediri Baptist Hospital - Yosh Briantito; Andreas Wahyudi (Green Publisher Indonesia, 2025)
Peritonitis due to perforation of hollow organs is a surgical emergency condition with high mortality and morbidity rates. The Mannheim Peritonitis Index (MPI) has been developed as a clinical prediction tool for the risk of complications, but has not been widely evaluated locally in the context of regional health care facilities. Assessing the effectiveness of the Mannheim Peritonitis Index (MPI) as a predictor of mortality and morbidity of peritonitis patients due to perforation of hollow organs at Kediri Baptist Hospital. This retrospective study analyzed 104 cases of peritonitis due to perforation of hollow organs who underwent exploratory laparotomy between January 2021 and February 2025. Data were collected from electronic medical records and analyzed using the Chi-Square test, Odds Ratio, and Mann-Whitney U Test. MPI was classified into low–medium (<27) and high (≥27) risk, and was analyzed for its relationship with age, sex, morbidity, and mortality. The majority of patients were 30–60 years old, with an average age of 40.13 years. Age >50 years and female sex were significantly associated with high MPI (p=0.010 and p=0.045). Generalisata peritonitis increased the risk of morbidity (p=0.009), and renal failure correlated with mortality (p=0.012). The MPI threshold value ≥15.50 had a sensitivity of 65.22% and a specificity of 59.26% for morbidity, as well as a sensitivity of 50% and a specificity of 53.92% for mortality. The AUC value indicates that the predictability of MPI is moderate (morbidity: 0.610; mortality: 0.554).